Analisi Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Optik - Al Anshori, Imam; Parno, Parno; Hidayat, Arif (Universitas Nahdlatul Ulama Blitar, 2024)
: Optics is a branch of physics related to complex and abstract daily life technology. Critical thinking skills can make a very meaningful contribution to students in understanding abstract material such as optics. Therefore, this study aims to describe students' critical thinking skills in the context of optics learning. Descriptive method with qualitative approach was applied to 108 students of class XII MIPA. The research instrument consisted of 5 description questions. The results showed that the average critical thinking ability of students was 55.28 (medium category). When viewed from each sub-matter, the percentage of students who fall into the low critical thinking ability category is 53.7% (light reflection material) and 54.6% (light refraction material). In a more in-depth analysis, the percentage of students' critical thinking skills on each indicator also tended to be higher in the low critical thinking ability group, with values of 66.7% (interpretation indicator), 71.3% (analysis indicator), 65.7% (inference indicator), 86.1% (evaluation indicator), and 80.6% (explanation indicator). The implications of the results of this study indicate the need to apply learning methods that can train students in solving problems in everyday life that are general and complex, such as PjBL and the STEAM approach.